Domain Decomposition Methods in Science and Engineering XX - Bank, Randolph; Holst, Michael; Widlund, Olof.; Xu, Jinchao; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
These are the proceedings of the 20th international conference on domain decomposition methods in science and engineering. Domain decomposition methods are iterative methods for solving the often very large linearor nonlinear systems of algebraic equations that arise when various problems in continuum mechanics are discretized using finite elements. They are designed for massively parallel computers and take the memory hierarchy of such systems in mind. This is essential for approaching peak floating point performance. There is an increasingly well developed theory whichis having a direct impact on the development and improvements of these algorithms.
Preface -- Part I: Plenary Presentations -- Part II: Minisymposia -- Part III: Contributed Presentations.
Keywords: Mathematics; Computer aided design; Differential equations, partial; Computer science -- Mathematics; Computer science; Mathematics; Computational Mathematics and Numerical Analysis; Computational Science and Engineering; Partial Differential Equations; Computer-Aided Engineering (CAD, CAE) and Design